Peningkatan Pemahaman dan Keterampilan Sains Siswa Melalui Eksperimen Kimia Berbasis Bahan Sederhana di SMA Negeri 2 Bengkulu Selatan - Yoravika Dwiwibangga; Vicka Andini; Evi Maryanti; Agus Martono Hadi Putranto; Freshka Aulia Aulia Dwi (Indonesian Journal of Community Empowerment and Service (ICOMES), 2026)
The community service program, “Education and Learning of Chemical Reactions through Simple Science Experiments at SMA Negeri 2 Bengkulu Selatan,” aims to address the limitations of laboratory facilities in chemistry learning. This activity involved 37 students to enhance their understanding of chemistry concepts, practical skills, and interest in chemistry through experiments using natural materials and household waste. The implementation methods included the delivery of basic theory, demonstrations, pretests, and hands-on practice with three simple experiments: identification of vitamin C using iodine, making a lava lamp, and recycling used cooking oil into candles, followed by a posttest. Evaluation results from the pretest and posttest showed a significant improvement in students’ understanding. A total of 90.32% of students stated that they actively participated in the experiments and experienced a significant increase in their understanding of chemical reaction concepts after the practice. This program also strengthened the collaboration between the Chemistry Undergraduate Study Program, Faculty of Mathematics and Natural Sciences, University of Bengkulu, and the partner school through educational and interactive activities. The program outputs include a scientific publication in an ISSN-registered community service journal, an activity video, news publications on the Chemistry Study Program’s website and social media, and an intellectual property registration. Keywords: science experiment; chemical reaction; vitamin C; lava lamp; used cooking oil.